Bacterial cellulose shifts transcriptome and proteome of cultured endothelial cells towards native differentiation - Feil, Gerhard; Arnold, Caroline (Molecular & cellular proteomics, 2017)
Preserving the native phenotype of primary cells in vitro is a complex challenge. Recently, hydrogel-based cellular matrices have evolved as alternatives to conventional cell culture techniques. We developed a bacterial cellulose-based aqueous gel-like biomaterial, dubbed Xellulin, which mimics a cellular microenvironment and seems to maintain the native phenotype of cultured and primary cells. When applied to human umbilical vein endothelial cells (HUVEC), it allowed the continuous cultivation of cell monolayers for more than one year without degradation or dedifferentiation. To investigate the impact of Xellulin on the endothelial cell phenotype in detail, we applied quantitative transcriptomics and proteomics and compared the molecular makeup of native HUVEC, HUVEC on collagen-coated Xellulin and collagen-coated cell culture plastic (polystyrene).Statistical analysis of 12,475 transcripts and 7831 proteins unveiled massive quantitative differences of the compared transcriptomes and proteomes. K-means clustering followed by network analysis showed that HUVEC on plastic upregulate transcripts and proteins controlling proliferation, cell cycle and protein biosynthesis. In contrast, HUVEC on Xellulin maintained, by and large, the expression levels of genes supporting their native biological functions and signaling networks such as integrin, receptor tyrosine kinase MAP/ERK and PI3K signaling pathways, while decreasing the expression of proliferation associated proteins. Moreover, CD34-an endothelial cell differentiation marker usually lost early during cell culture - was re-expressed within 2 weeks on Xellulin but not on plastic. And HUVEC on Xellulin showed a significantly stronger functional responsiveness to a prototypic pro-inflammatory stimulus than HUVEC on plastic.Taken together, this is one of the most comprehensive transcriptomic and proteomic studies of native and propagated HUVEC, which underscores the importance of the morphology of the cellular microenvironment to regulate cellular differentiation, and demonstrates, for the first time, the potential of Xellulin as versatile tool promoting an in vivo-like phenotype in primary and propagated cell culture.